Efektivitas Penyidikan Tindak Kriminal di Kepolisian Sektor Ilir Barat I Palembang - DB, Timbul Petrus; Lisdiana, Lisdiana; Febrianza, Muhammad (@-Publik: Jurnal Administrasi Publik, 2024)
This research aims to evaluate the effectiveness of criminal investigations at the Ilir Barat I Palembang Sector Police. Effective investigations are key in law enforcement, especially in ensuring that the judicial process runs fairly and efficiently. This research uses a qualitative descriptive method by collecting data through interviews with investigators, analysis of case documents, and direct observation of the investigation process. The research results show that the effectiveness of investigations at the Ilir Barat I Palembang Police Sector is at a fairly good level, but there are still several challenges, such as limited resources, high workload, and lack of supporting facilities. Factors that support the effectiveness of investigations include the experience and competence of investigators, as well as cooperation with other parties, including the community and related institutions. However, obstacles such as complex bureaucratic procedures and technical obstacles in collecting evidence often slow down the investigation process. The recommendations given include increasing the capacity of investigators through training, improving supporting facilities, and simplifying bureaucratic procedures to improve the efficiency and quality of investigations at the Ilir Barat I Palembang Sector Police. With these steps, it is hoped that the investigation process can run more effectively and make a greater contribution to law enforcement efforts.